Literature Study: Application of PBL-STEM on Simple Machine Topic to Improve Critical Thinking Skills - Yoga Parenta; Mohammad Masykuri; Sulistyo Saputro (Postgraduate, University of Mataram, 2022)
This study aims to know and describe the application of problem-based learning integrated science, technology, engineering, and mathematics or commonly known as PBL-STEM on Simple Machine Topic to Improve Critical Thinking Skills. The method used in this research is qualitative research with data collection techniques, namely literature studies. The process of collecting data in this study is by looking for theoretical references that are relevant to the problems found. The data obtained is then analyzed with descriptive analysis methods. Based on the analysis of the data used, the result showed an increase in critical thinking skills owned by students, which can be seen from the N-gain score obtained. These results are also supported by other relevant studies. Based on a literature review, it can be concluded that the application of PBL-STEM on simple machine subjects can improve critical thinking skills